Dynamics alteration of the gut microbiota and faecal metabolomes in very low or extremely low birth weight infants: a Chinese single-center, prospective cohort study - Liu, Ling; Chen, Chaohong; Li, YeShan; Ao, Dang; Wu, Jiayuan; Cai, Nali; Li, Wen; Xiang, Min (Frontiers in Microbiology, 2024)
Objective: The aim of this study is to comprehensively investigate the temporal dynamics of fecal gut microbiota and metabonomics in early postnatal with a focus on very low or extremely low birth weight (VLBW/ELBW) infants.Methods: We collected fecal samples from 157 VLBW/ELBW infants at three time points: days 1, 14, and 28 in a prospective cohort study. The fecal microbial diversity, abundance, composition, and metabolomic analyses were determined using 16S rRNA sequencing and liquid chromatography tandem mass spectrometry (LC-MS/MS). Microbiome functional analyses were conducted utilizing PICRUSt2. The ecological association networks were employed to investigate the interactions between gut microbiota and identify the core genus within 28 days of birth, as well as to unveil correlations between taxa and metabolites.Result: (1) The alpha diversity of gut microbiota significantly decreased from D1 to D28, accompanied by an interrupted trajectory lacking obligate anaerobes. At the phylum level, the 16S RNA sequencing results showed an increase in Proteobacteria and a decrease in Firmicutes and Bacteroidota from D1 to D28. At the genus level, there was a decrease in the relative abundance of Staphylococcus, Acinetobacter and Ureaplasma, with Klebsiella and Enterococcus emerging as the most abundant genera. (2) The analysis revealed a total of 561 metabolic markers that exhibited significant and distinct alterations between D1 and D14. (3) Ecological association networks revealed that the gut microbiota in D1 exhibited a significantly higher degree of microbial interactions compared to those in D14 and D28. Additionally, Enterococcus, Klebsiella, and Enterobacter were major contributors to the co-occurring network at these three time points. (4) Steroid hormone biosynthesis, including tetrahydrocortisone, androsterone glucuronide, androstenedione and etiocholanolone glucuronide, decreased within 28 days after birth.We have successfully demonstrated a significant dysbiosis in the gut microbiota and a subsequent decrease in its diversity within four weeks postpartum in VLBW/ELBW infants.Monitoring the gut microbiota of VLBW/ELBW infants and promptly rectifying dysbiosis in the early stages may represent a potential therapeutic strategy.